1994
DOI: 10.1159/000246888
|View full text |Cite
|
Sign up to set email alerts
|

Localized Scleroderma after Exposure to Organic Solvents

Abstract: A 26-year-old female developed plaques characteristic of morphea on the volar surfaces of the forearms and on the dorsal surfaces on the ankles following an exposure to trichloroethylene, tetrachloroethylene and other solvents by inhalation. Exposure to chemicals has been known to be important as a provoking factor of systemic sclerosis. This patient shows that exposure to solvents could provoke localized scleroderma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 7 publications
0
12
0
2
Order By: Relevance
“…An exposure to aliphatic or hydrocarbon solvents, including trichloroethylene, perchloroethylene, toluene, benzene and xylene, and also white spirits, diesel and aromatic mixes, seems to be an important provoking factor for scleroderma-related disorders in different parts of the world [1,[3][4][5][6][7][8][9][10][11][12], including Hungary [5,6,[13][14][15]. Among the solvents trichloroethylene is a considerable provoking factor [6,9,10,13,[16][17][18]. Other agents, such as perchloroethylene, benzene [6,14], other organic compounds including amines [4], and formaldehyde derivatives [4] are also capable of provoking scleroderma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exposure to aliphatic or hydrocarbon solvents, including trichloroethylene, perchloroethylene, toluene, benzene and xylene, and also white spirits, diesel and aromatic mixes, seems to be an important provoking factor for scleroderma-related disorders in different parts of the world [1,[3][4][5][6][7][8][9][10][11][12], including Hungary [5,6,[13][14][15]. Among the solvents trichloroethylene is a considerable provoking factor [6,9,10,13,[16][17][18]. Other agents, such as perchloroethylene, benzene [6,14], other organic compounds including amines [4], and formaldehyde derivatives [4] are also capable of provoking scleroderma.…”
Section: Introductionmentioning
confidence: 99%
“…Among the solvents trichloroethylene is a considerable provoking factor [6,9,10,13,[16][17][18]. Other agents, such as perchloroethylene, benzene [6,14], other organic compounds including amines [4], and formaldehyde derivatives [4] are also capable of provoking scleroderma. Anti-Scl-70 positive scleroderma cases seem to be more susceptible to the effects of solvents [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Human TCE exposure (both occupational and environmental) has been linked to several autoimmune diseases (scleroderma, systemic lupus erythematosus, hepatitis and diabetes [3][4][5][6][7][8][9][10][11]) and hypersensitivity disorders [12][13][14]. By using a female MRL+/+ mouse model, we have shown that chronic exposure to TCE during adulthood promotes autoimmune hepatitis that corresponds to idiopathic autoimmune hepatitis in humans, that is, T-cell infiltration of the liver and development of antibodies specific for liver microsomal proteins [15,16].…”
mentioning
confidence: 99%
“…kommen [13]. Der Kontakt zu verschiedenen organischen Lösungsmittel kann auch ein Provokationsfaktor für die Sklerodermie darstellen [14]. So führte z.…”
Section: Diskussionunclassified
“…So führte z. B. eine langjährige inhalative Exposition gegenüber Trichlorethylen und Tetrachchlorethylen zur Entwicklung einer zirkumskripten Sklerodermie [14]. Es sind auch Fälle von Sklerodermie nach langjähriger beruflicher Exposition gegenüber Trichlorethylen beschrieben worden [15].In einer groß angelegten wissenschaftlichen Fallkontrollstudie wurde untersucht, ob ein beruflicher Kontakt mit organischen Lö-sungsmitteln mit einem erhöhten Risiko für die Entwicklung einer Sklerodermie verbunden ist [16].Die Autoren dieser Studie kommen zu dem Schluss, dass die Ergebnisse der vorgelegten Untersuchung offensichtlich dafür sprechen, dass eine berufliche Belastung mit organischen Lö-sungsmitteln mit einem erhöhten Risiko der Entwicklung einer Sklerodermie verbunden ist [16].…”
Section: Diskussionunclassified